Pemberdayaan Masyarakat Dalam Program Pengembangan Bimbingan Belajar Masyarakat (Studi Kasus Desa Waruk, Kec Karangbinangun Lamongan) - Isna Ayu Safitri Kusuma Dewi; Fibia Sentauri Cahyaningrum; Dina Maysaroh; Presti Belinda (Jurnal Pengabdian Masyarakat Nusantara, 2022)
One of the problems in the Waruk Village community, Karangbinangun District, Lamongan Regency, is the lack of awareness of the potential around them that they might be able to use as additional resources that might be useful for the education of the Waruk Village community. With this potential, the people of Waruk Village can be more able to build and develop a more advanced learning system in Waruk Village and can help people who are less educated in Waruk Village.